Relaxin Can Mediate Its Anti-Fibrotic Effects by Targeting the Myofibroblast NLRP3 Inflammasome at the Level of Caspase-1 - Pinar, Anita A.; Yuferov, Alexander; Gaspari, Tracey A.; Samuel, Chrishan S. (Frontiers in Pharmacology, 2020)
Introduction: The NLRP3 inflammasome produces interleukin (IL)-1β and IL-18, which when chronically activated by transforming growth factor (TGF)-β1, contribute to fibrosis. The recombinant form of the anti-fibrotic hormone, relaxin (RLX), suppresses the pro-fibrotic influence of TGF-β1 and toll-like receptor (TLR)-4 on NLRP3 inflammasome priming and activity in human cardiac myofibroblasts and mice with cardiomyopathy. However, whether RLX also modulates components of the myofibroblast NLRP3 inflammasome remains unknown. Methods and Results: Stimulation of a human dermal fibroblast (HDF) cell line with TGF-β1 (5ng/mL; to promote myofibroblast (HDMF) differentiation), LPS (100ng/mL; to prime the NLRP3 inflammasome) and ATP (5mM; to activate the NLPR3 inflammasome) (T+L+A) significantly increased NLRP3 inflammasome priming and activity after 8 and 72 h; and α-SMA expression (myofibroblast differentiation) and collagen-I deposition after 72 h. siRNA-induced knock-down of NLRP3 inflammasome priming components (NLRP3, ASC, caspase-1) in T+L+A-stimulated HDMFs for 24 h, completely knocked-down each component after 72 h. RLX (100ng/mL) administration to T+L+A-stimulated HDMFs after control, NLRP3 or ASC siRNA transfection, equivalently suppressed IL-1β, pro-IL-18, α-SMA and collagen-I protein levels (by 40-50%; all p<0.05 vs T+L+A) after 72 h, as determined by Western blotting. These RLX-induced effects were abrogated by siRNA knock-down of caspase-1. Conclusion: The anti-fibrotic actions of RLX appear to require modulation of caspase-1 within the myofibroblast NLRP3 inflammasome.